Even if I did something awful - Hazen, Barbara Shook; Kincade, Nancy (New York : Aladdin Paperbacks, 1992)
Before revealing the awful thing she did, a child tries to get her mother's assurance of love, no matter what.
3.3
K-3
K-3
School Library Journal
Book Links (A.L.A.)
Bulletin (Center for Children's books)
Keywords: Parent and child -- Fiction; Love -- Fiction; Parent-child relationship -- Fiction; Love -- Fiction